Evaluating cardiac echocardiographic changes with levothyroxine in hypothyroid patients: a systematic review and meta-analysis - Li, Yanyan (Frontiers in Endocrinology, 2026)
BackgroundWhile levothyroxine (L-T4) therapy is standard for hypothyroidism, its direct effects on specific echocardiographic parameters of cardiac function remain underexplored in comprehensive meta-analyses.MethodsWe systematically searched multiple databases up to June 2025 for randomized controlled trials and prospective cohort studies assessing L-T4 therapy on echocardiographic parameters in hypothyroid adults. Data on cardiac indices, intervention details, follow-up, and disease types were extracted. Risk of bias was assessed using standard tools. A random-effects model calculated mean differences (MDs) and assessed heterogeneity. Subgroup analyses evaluated treatment type, follow-up duration, and underlying disease.ResultsSix studies (2 RCTs and 4 cohort studies) were included. Overall, L-T4 intervention did not significantly alter the LV Tei Index (MD = 0.0214, 95% CI: -0.0294 to 0.0722, p=0.4083) or LVEF (MD = -0.2258, 95% CI: -0.8990 to 0.4475, p=0.5110). However, a statistically significant increase in Mitral E velocity (MD = -0.0646, 95% CI: -0.1138 to -0.0154, p=0.0100) and Mitral A velocity (MD = -0.0646, 95% CI: -0.1138 to -0.0154, p=0.0100) was observed. Subgroup analyses for LV Tei Index showed a statistically significant improvement in the 12-month follow-up subgroup (MD = 0.0672, 95% CI: 0.0161 to 0.1183) and in congenital hypothyroidism (MD = 0.0300, 95% CI: 0.0044 to 0.0556). For LVEF, a statistically significant increase was found in the 12-week follow-up subgroup (MD = -7.9300, 95% CI: -14.4844 to -1.3756) and the overt hypothyroidism subgroup (MD = -7.9300, 95% CI: -14.4844 to -1.3756). The effect of L-T4 on Mitral E and Mitral A velocities varied significantly across disease types (p=0.0304 for both), with a significant increase noted in the congenital hypothyroidism subgroup for both. No significant change was observed in the E/A ratio (MD = -0.0058, 95% CI: -0.0360 to 0.0244, p=0.7058), with no significant subgroup differences.ConclusionL-T4 exerts differential effects on echocardiographic measures of cardiac function, with specific improvements influenced by follow-up duration and underlying etiology.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, CRD420251274519.